A novel IgE-binding epitope of cat major allergen, Fel d 1 - Natt Tasaniyananda (2018)
© 2016 Elsevier Inc. All rights reserved. Information on the antigenic repertoire, especially the IgE-binding epitopes of an allergen is important for understanding the allergen induced immune response and cross-reactivity, as well as for generating the hypoallergenic variants for specific component resolved immunotherapy/diagnosis (CRIT and CRD). Data on the IgE-binding epitopes of cat allergens are scarce. In this study, a novel IgE-binding epitope of the cat major allergen, Fel d 1, was identified. Mouse monoclonal antibody (MAb) specific to the Fel d 1 was produced. Computerized intermolecular docking was used for determining the residues of the Fel d 1 bound by the specific MAb. The presumptive surface exposed residues of the Fel d 1 intrigued by the MAb are located on the chain 1. They are: L34 and T37 (helix 1); T39 (between helices 1 and 2); P40, E42 and E45 (helix 2); R61, K64, N65 and D68 (helix 3); and E73 and K76 (helix 4). The MAb competed efficiently with the cat allergic patients' serum IgE for Fel d 1 binding in the competitive IgE binding assay, indicating allergenicity of the MAb epitope. The newly identified allergenic epitope of the Fel d 1 is useful in a design of the CRIT and CRD for cat allergy.